Experimental results of a High-Temperature-ATES field test: Induced convection, heat conduction and groundwater flow as efficiency-reducing processes - Johannes Nordbeck; Götz Hornbruch; Klas Lüders; Jan Niklas Nordheim; Ulrike Werban; Carsten Vogt; Hans Richnow; Sebastian Bauer (Geothermics, 2026)

Integrating hydraulic and thermal constraints for ATES well placements: An analytical approach - Jan Niklas Nordheim; Christof Beyer; Sebastian Bauer (Hydrogeology Journal, 2026)
Aquifer thermal energy storage (ATES) mitigates the seasonal mismatch between summertime heat supply and wintertime heat demand, contributing to decarbonization of the heating and cooling sector. Conventional low-temperature ATES design targets high-transmissivity aquifers to achieve the pumping rates needed to meet energy demand. If geological constraints or competing subsurface uses require storage in lower-transmissivity formations, pumping rates may be restricted to limit hydraulic head changes or reduce the risk of well screen particle clogging. This restriction would increase the number of well doublets and potentially make well field layout a critical design challenge. To address this complexity at an early planning stage, an analytical approach is presented that determines the minimum number and distance of ATES well doublets assuming a checkerboard or a lane layout. The approach combines thermal and hydraulic constraints by determining a minimum well distance derived from the thermal radius and a maximum well distance necessary to limit pumping-induced head changes, explicitly accounting for hydraulic superposition effects in multi-doublet well fields. Applying this approach to a planned low-temperature ATES at Kiel University, Germany, shows that the checkerboard layout achieves the target pumping rate of 200 m 3 /h with nine well doublets, whereas the lane layout requires 11 well doublets. The analysis also indicates that reducing the distance between wells of the same type in low-transmissivity aquifers significantly increases the number of well doublets. The approach provides a practical tool for preliminary ATES design, supporting informed well field configuration under hydraulic constraints.

Informational nudges or incentives? A field experiment on vegetarian choices. - Alice Pizzo; Jan M. Bauer; Lucia A. Reisch (Ecological Economics, 2026)

Perceived plasticity of climate-relevant behaviors and policy support among high- and lower-income individuals - Kristian S. Nielsen; Fabian Dablander; Ramit Debnath; Charles A. Emogor; Sakshi Ghai; Wencke Gwozdz; Ulf J.J. Hahnel; Wilhelm Hofmann; Jan M. Bauer (Global Environmental Change, 2026)

EDTA-induced remobilization of lead from suspended particulate matter in contaminated water samples from the Innerste River: a statistical evaluation - Jan Klaus Hinrichs; Markus Herrmann; Aaron Bauer; Dieter Steffen (Environmental Science and Pollution Research, 2026)
Ethylenediaminetetraacetic acid (EDTA), extensively used across multiple industries, has long been discussed for its potential to enhance heavy metal mobility in aquatic systems, with studies yielding contradictory results. This study examines the remobilization of particle-bound lead from suspended particulate matter (SPM) in the Innerste River (Lower Saxony, Germany), which is affected by historical mining and known for substantial Pb contamination. Using real river water containing its native SPM to preserve the chemical matrix of the system, we assessed Pb partitioning between total and dissolved phases to evaluate EDTA’s remobilization potential. Baseline dissolved lead concentrations reached up to 1.8 µg L −1 (median 0.69 µg L −1 ). Across all batch experiments, a measurable increase in the dissolved Pb fraction occurred only at EDTA concentrations far exceeding those measured in the river (0.68–3.8 µg L −1 ). Bayesian concentration–response modelling yielded no-effect concentrations (NEC) between 210 and 530 µg L −1 . Complementary speciation modelling showed that shifts in Pb speciation occur only at EDTA concentrations near the experimentally derived NEC values. These findings show that current EDTA concentrations in the Innerste are unlikely to remobilize Pb from SPM. The study also provides a statistically supported NEC estimate based on batch experiments using unaltered river water containing its naturally present SPM. To our knowledge, this is the first application of Bayesian NEC modelling to EDTA-induced Pb remobilization.

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Speeding up fermionic lattice calculations with photonic accelerated inverters - Felipe Attanasio; Marc Bauer; Jelle Dijkstra; Timoteo Lee; Jan M. Pawlowski; Wolfram Pernice; Frank Brückerhoff-Plückelmann (Computer Physics Communications, 2025)

Limited efficiency of wet scrubbers in reducing the environmental impact of ship-emitted particles - Lukas Anders; Martin Bauer; Seongho Jeong; Marco Schmidt; Haseeb Hakkim; Aleksandrs Kalamašņikovs; Ellen Iva Rosewig; Julian Schade; Robert Irsig; Sven Ehlert; Jan Bendl; Mohammad Reza Saraji-Bozorgzad; et al. (Environmental Chemistry Letters, 2025)
Sulfur dioxide pollution by ship emissions can be efficiently decreased by using exhaust gas scrubbers, yet particles can pass through the scrubber and be released into the atmosphere. Here, we studied the impact of using a wet scrubber on the composition of particle emissions, by single-particle analysis. At low engine loads, results show no significant changes in particle composition of metals, salts, and polycyclic aromatic hydrocarbons (PAH). At high engine loads, the scrubber reduced soot and PAH signatures about fourfold. Particles passing through the scrubber undergo minimal chemical changes, except for sulfate uptake. The cleaning effect of wet scrubbers is attributed to the removal of water-soluble gas-phase compounds, diffusion-dominated uptake of ultrafine particles, and wet deposition of coarse particles. The scrubber has little effect on reducing the health and environmental impacts of the remaining particles that pass through it. These emitted particles, primarily in the 60–200 nm size range, constitute a significant portion of the inhalable particle mass and have the potential for long-range transport.

Current research on aquifer thermal energy storage (ATES) in Germany - Ruben Stemmle; Alireza Arab; Sebastian Bauer; Christof Beyer; Guido Blöcher; Claire Bossennec; Maximilian Dörnbrack; Florian Hahn; Philip Jaeger; Stefan Kranz; Alexandra Mauerberger; Jan Niklas Nordheim; et al. (Grundwasser, 2025)
This paper reviews the current research on aquifer thermal energy storage (ATES) and mine thermal energy storage (MTES) in Germany providing descriptions of 3 low-temperature ATES (LT-ATES), 8 high-temperature ATES (HT-ATES), and 2 MTES research sites. While the overview reveals a diverse field of investigations spanning various spatial scales, research objectives, and methodologies, the predominant focus is limited to early-stage research with low technology readiness levels (TRL). The high number of HT-ATES research sites suggests greater research interest compared to LT-ATES. The integration of ATES into district heating (DH) grids in particular is a prominent research focus, yet almost none of the projects are specifically intended for practical implementation. Future research should therefore prioritize real-world demonstration projects and identify key locations, which is crucial for showcasing the benefits of ATES. The need for a streamlined regulatory framework that addresses environmental risks and ensures installation quality and efficient permit procedures is also discussed.

Thermo- and light responsive microgels for efficient brackish and seawater forward osmosis desalination - Amir Jangizehi; Jan Eckhardt; Karolina Izabela Borkowska; Zsolt Dallos; Melanie Bauer; Hasan Salehi; Reza Razavi; Alireza Shakeri; Seyed Abdollatif Hashemifard; Sebastian Seiffert (Desalination, 2025)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Detecting Maritime GPS Spoofing Attacks Based on NMEA Sentence Integrity Monitoring - Julian Spravil; Christian Hemminghaus; Merlin von Rechenberg; Elmar Padilla; Jan Bauer (Journal of Marine Science and Engineering, 2023)
Today’s maritime transportation relies on global navigation satellite systems (GNSSs) for accurate navigation. The high-precision GNSS receivers on board modern vessels are often considered trustworthy. However, due to technological advances and malicious activities, this assumption is no longer always true. Numerous incidents of tampered GNSS signals have been reported. Furthermore, researchers have demonstrated that manipulations can be carried out even with inexpensive hardware and little expert knowledge, lowering the barrier for malicious attacks with far-reaching consequences. Hence, exclusive trust in GNSS is misplaced, and methods for reliable detection are urgently needed. However, many of the proposed solutions require expensive replacement of existing hardware. In this paper, therefore, we present MAritime Nmea-based Anomaly detection (MANA), a novel low-cost framework for GPS spoofing detection. MANA monitors NMEA-0183 data and advantageously combines several software-based methods. Using simulations supported by real-world experiments that generate an extensive dataset, we investigate our approach and finally evaluate its effectiveness.

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

Early post-discharge mortality in CAP: frequency, risk factors and a prediction tool - Verena Glöckner; Mathias W. Pletz; Gernot Rohde; Jan Rupp; Martin Witzenrath; Grit Barten-Neiner; Martin Kolditz; M. Dreher; C. Cornelissen; W. Knüppel; D. Stolz; N. Suttorp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
There are few data on mortality after discharge with community-acquired pneumonia (CAP). Therefore, we evaluated risk factors for 30-day post-discharge mortality after CAP. We included all patients of the prospective multi-national CAPNETZ study between 2002 and 2018 with (1) hospitalized CAP, (2) survival until discharge, and (3) complete follow-up data. The study endpoint was death within 30 days after discharge. We evaluated risk factors including demographics, comorbidities, admission CAP severity, and laboratory values and treatment-related factors in uni- and multivariable analyses. A total of 126 (1.6%) of 7882 included patients died until day 30 after discharge, corresponding to 26% of all 476 deaths. After multivariable analysis, we identified 10 independent risk factors: higher age, lower BMI, presence of diabetes mellitus, chronic renal or chronic neurological disease (other than cerebrovascular diseases), low body temperature or higher thrombocytes on admission, extended length of hospitalization, oxygen therapy during hospitalization, and post-obstructive pneumonia. By addition these factors, we calculated a risk score with an AUC of 0.831 (95%CI 0.822–0.839, p < 0.001) for prediction of post-discharge mortality. Early post-discharge deaths account for ¼ of all CAP-associated deaths and are associated with patient- and CAP-severity-related risk factors. Additional studies are necessary to replicate our findings in independent cohorts. Study registration: NCT 02139163.

Anomaly Detection in Maritime AIS Tracks: A Review of Recent Approaches - Konrad Wolsing; Linus Roepert; Jan Bauer; Klaus Wehrle (Journal of Marine Science and Engineering, 2022)
The automatic identification system (AIS) was introduced in the maritime domain to increase the safety of sea traffic. AIS messages are transmitted as broadcasts to nearby ships and contain, among others, information about the identification, position, speed, and course of the sending vessels. AIS can thus serve as a tool to avoid collisions and increase onboard situational awareness. In recent years, AIS has been utilized in more and more applications since it enables worldwide surveillance of virtually any larger vessel and has the potential to greatly support vessel traffic services and collision risk assessment. Anomalies in AIS tracks can indicate events that are relevant in terms of safety and also security. With a plethora of accessible AIS data nowadays, there is a growing need for the automatic detection of anomalous AIS data. In this paper, we survey 44 research articles on anomaly detection of maritime AIS tracks. We identify the tackled AIS anomaly types, assess their potential use cases, and closely examine the landscape of recent AIS anomaly research as well as their limitations.

Sediment generation and soil mound denudation in areas of high-density tree throw along a river valley in the Jura Mountains, Switzerland - Philip Greenwood; Jan Bauer; Nikolaus J. Kuhn (Journal of Mountain Science, 2021)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Risk to residents, infrastructure, and water bodies from flash floods and sediment transport - Miroslav Bauer; Tomas Dostal; Josef Krasa; Barbora Jachymova; Vaclav David; Jan Devaty; Ludek Strouhal; Pavel Rosendorf (Environmental Monitoring and Assessment, 2019)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The value of bioenergy in low stabilization scenarios: an assessment using REMIND-MAgPIE - David Klein; Gunnar Luderer; Elmar Kriegler; Jessica Strefler; Nico Bauer; Marian Leimbach; Alexander Popp; Jan Philipp Dietrich; Florian Humpenöder; Hermann Lotze-Campen; Ottmar Edenhofer (Climatic Change, 2014)

Land-use transition for bioenergy and climate stabilization: model comparison of drivers, impacts and interactions with other land use based mitigation options - Alexander Popp; Steven K. Rose; Katherine Calvin; Detlef P. Van Vuuren; Jan Phillip Dietrich; Marshall Wise; Elke Stehfest; Florian Humpenöder; Page Kyle; Jasper Van Vliet; Nico Bauer; Hermann Lotze-Campen; et al. (Climatic Change, 2014)

Induction of Experimental Autoimmune Encephalomyelitis With Recombinant Human Myelin Oligodendrocyte Glycoprotein in Incomplete Freund’s Adjuvant in Three Non-human Primate Species - Krista G. Haanstra; S. Anwar Jagessar; Anne-Laure Bauchet; Mireille Doussau; Claire-Maëlle Fovet; Nicole Heijmans; Sam O. Hofman; Jennifer van Lubeek-Veth; Jeffrey J. Bajramovic; Yolanda S. Kap; Jon D. Laman; Hélène Touin; et al. (Journal of Neuroimmune Pharmacology, 2013)

The Different Clinical Effects of Anti-BLyS, Anti-APRIL and Anti-CD20 Antibodies Point at a Critical Pathogenic Role of γ-Herpesvirus Infected B Cells in the Marmoset EAE Model - S. Anwar Jagessar; Zahra Fagrouch; Nicole Heijmans; Jan Bauer; Jon D. Laman; Luke Oh; Thi Migone; Ernst J. Verschoor; Bert A. ’t Hart (Journal of Neuroimmune Pharmacology, 2013)

Erratum to: Antibodies Against Human BLyS and APRIL Attenuate EAE Development in Marmoset Monkeys - S. Anwar Jagessar; Nicole Heijmans; Luke Oh; Jan Bauer; Erwin L. A. Blezer; Jon D. Laman; Thi-Sau Migone; Matt N. Devalaraja; Bert A. ’t Hart (Journal of Neuroimmune Pharmacology, 2013)

Well Field Management Using Multi-Objective Optimization - Annette K. Hansen; Harrie-Jan Hendricks Franssen; Peter Bauer-Gottwein; Henrik Madsen; Dan Rosbjerg; Hans-Peter Kaiser (Water Resources Management, 2013)

Reuteran and levan as carbohydrate sinks in transgenic sugarcane - Rolene Bauer; Carin E. Basson; Jan Bekker; Iban Eduardo; Johann M. Rohwer; Lafras Uys; Johannes H. van Wyk; Jens Kossmann (Planta, 2012)

Antibodies Against Human BLyS and APRIL Attenuate EAE Development in Marmoset Monkeys - S. Anwar Jagessar; Nicole Heijmans; Jan Bauer; Erwin L. A. Blezer; Jon D. Laman; Thi-Sau Migone; Matt N. Devalaraja; Bert A. ’t Hart (Journal of Neuroimmune Pharmacology, 2012)

Manipulation of l-ascorbic acid biosynthesis pathways in Solanum lycopersicum: elevated GDP-mannose pyrophosphorylase activity enhances l-ascorbate levels in red fruit - Christelle Cronje; Gavin M. George; Alisdair R. Fernie; Jan Bekker; Jens Kossmann; Rolene Bauer (Planta, 2012)

Discrepant Effects of Human Interferon-gamma on Clinical and Immunological Disease Parameters in a Novel Marmoset Model for Multiple Sclerosis - S. Anwar Jagessar; Bruno Gran; Nicole Heijmans; Jan Bauer; Jon D. Laman; Bert A. ‘t Hart; Cris S. Constantinescu (Journal of Neuroimmune Pharmacology, 2012)

Genetically Engineered Mesenchymal Stem Cells as a Proposed Therapeutic for Huntington’s Disease - Scott D. Olson; Kari Pollock; Amal Kambal; Whitney Cary; Gaela-Marie Mitchell; Jeremy Tempkin; Heather Stewart; Jeannine McGee; Gerhard Bauer; Hyun Sook Kim; Teresa Tempkin; Vicki Wheelock; et al. (Molecular Neurobiology, 2012)

Effects of Early IL-17A Neutralization on Disease Induction in a Primate Model of Experimental Autoimmune Encephalomyelitis - Yolanda S. Kap; S. Anwar Jagessar; Nikki van Driel; Erwin Blezer; Jan Bauer; Marjan van Meurs; Paul Smith; Jon D. Laman; Bert A. ‘t Hart (Journal of Neuroimmune Pharmacology, 2011)

Encephalitis and epilepsy - Jan Bauer; Christian G. Bien (Seminars in Immunopathology, 2009)

Establishment and management of woody seedlings in gullies in a semi-arid environment (Tigray, Ethiopia) - Bert Reubens; Jean Poesen; Jan Nyssen; Yves Leduc; Amanuel Z. Abraha; Sarah Tewoldeberhan; Hans Bauer; Kindeya Gebrehiwot; Jozef Deckers; Bart Muys (Plant and Soil, 2009)

Comparative analysis of tumorbiology and CD133 positivity in primary and recurrent pancreatic ductal adenocarcinoma - Thilo Welsch; Shereen Keleg; Frank Bergmann; Luca Degrate; Sonja Bauer; Jan Schmidt (Clinical & Experimental Metastasis, 2009)

A rapid and easy to handle thermoluminescence based technique for evaluation of carbon tetrachloride-induced oxidative stress on rat hepatocytes - Anika Schumann; Alexander Bauer; Matthias Hermes; Matthias Gilbert; Jan G. Hengstler; Christian Wilhelm (Archives of Toxicology, 2009)

Munich Oktoberfest experience: remarkable impact of sex and age in ethanol intoxication - C. Binner; S. Selinski; M. J. Barysch; C. Pölcher; Wiebke Schormann; Matthias Hermes; Marc Brulport; Alexander Bauer; Claudia Rudolph; Essam Bedawy; Markus Schug; Klaus Golka; et al. (Archives of Toxicology, 2008)

Tracking of human cells in mice - Wiebke Schormann; Friedrich J. Hammersen; Marc Brulport; Matthias Hermes; Alexander Bauer; Claudia Rudolph; Markus Schug; Thomas Lehmann; Andreas Nussler; Hendrik Ungefroren; James Hutchinson; Fred Fändrich; et al. (Histochemistry and Cell Biology, 2008)

Cadmium, cobalt and lead cause stress response, cell cycle deregulation and increased steroid as well as xenobiotic metabolism in primary normal human bronchial epithelial cells which is coordinated by at least nine transcription factors - Felix Glahn; Wolfgang Schmidt-Heck; Sebastian Zellmer; Reinhard Guthke; Jan Wiese; Klaus Golka; Roland Hergenröder; Gisela H. Degen; Thomas Lehmann; Matthias Hermes; Wiebke Schormann; Marc Brulport; et al. (Archives of Toxicology, 2008)

Expression patterns and novel splicing variants of glutathione-S-transferase isoenzymes of human lung and hepatocyte cell lines - Mario Bauer; Olf Herbarth; Gabriela Aust; Jan G. Hengstler; Anja Dotzauer; Carolin Graebsch; Eike Schmuecking (Cell and Tissue Research, 2006)

T-cells in human encephalitis - Christian G. Bien; Jan Bauer (NeuroMolecular Medicine, 2005)

Increased transgene integration efficiency upon microinjection of DNA into both pronuclei of rabbit embryos - Peter Chrenek; Dusan Vasicek; Alexander V. Makarevich; Rastislav Jurcik; Karin Suvegova; Vladimir Parkanyi; Miroslav Bauer; Jan Rafay; Angelika Batorova; Rekha K. Paleyanda (Transgenic Research, 2005)

Tomato spotted wilt virus (TSWV) infection of Physcomitrella patens gametophores - Saskia Hühns; Christel Bauer; Sven Buhlmann; Cornelia Heinze; Susanne von Bargen; Martina Paape; Jan-Wolfhard Kellmann (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Platform environments, microfacies and systems tracts of the upper Cenomanian-lower Santonian of Sinai, Egypt - Jan Bauer; Jochen Kuss; Thomas Steuber (Facies, 2002)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)